Pengaruh Parent-Child Relationship terhadap Aktualisasi Peserta Didik Siswa Sekolah Dasar - Hadi, Abdul; Hanifah, Hana Qoidah (Arden Jaya Publisher, 2025)
This research aims to find out how much influence the parent-child relationship has on the self-actualization of students at Kledokan Kalasan Elementary School. The method used is a quantitative approach with a correlational research design. The sampling technique used is saturated sampling. The research sample consisted of 43 students. Data was collected through questionnaires distributed to subjects to measure parent-child relationship and self-actualization variables. The results of the analysis show that the parent-child relationship variable has an average value of 61.2791, while the average value for student self-actualization is 55.1628. It is known that the linearity test results have a sig value. deviation from linearity is 0.863 > 0.05, so there is a linear relationship between the two variables. Hypothesis testing using Pearson product moment correlation analysis produces a significance value of 0.006, which indicates a significant relationship between the two variables. The Pearson correlation coefficient value of 0.409 indicates a moderate correlation between parent-child relationship and self-actualization. The results of this research provide important implications for parents and educators to improve the quality of parent-child relationships as an effort to support the development of children's self-actualization.